THU0507 The Effect of Mycophenolate Mofetil (MMF) on Plasmablasts/Plasma Cells (PB/PC) and Serum Free Light Chain (FLC) Levels in Patients with Systemic Lupus Erythematosus (SLE). (10th June 2014) - Fassbinder, T.; Saunders, U.; Becker, H.; Jung, E.; Mickholz, E.; Schlüter, B.; Jacobi, A.M.
Abstract : Background: B cell hyperactivity is a hallmark of SLE. Differential blood counts, lymphocyte subsets and serological parameters are affected by disease activity and therapy. Objectives: To analyze the influence of MMF and other immunosuppressive drugs (ID) such as cyclophosphamide (CYC), azathioprine (AZA) or methotrexate (MTX) on B cell and PB/PC counts and FLCκ/λ levels. Methods: We performed a retrospective cross-sectional analysis of cellular and serological parameters in patients with SLE. Lupus patients with comparably high disease activity and either on induction or on maintenance therapy were subdivided into different treatment groups and compared to activity-matched patients not on ID (Tab. 1 ). All parameters were also determined repeatedly after induction therapy with CYC (n=24) or MMF (n=23) and in another subset of patients with MMF-responsive quiescent disease during drug taper or withdrawel (n=27). Results: Patients undergoing induction therapy with MMF had significantly lower PB/PC counts compared to patients treated with CYC or controls. In patients receiving maintenance therapy MMF was associated with a significantly lower PB/PC count compared to AZA and no ID. In addition PB/PC counts were also significantly lower in patients undergoing MTX treatment compared to controls. Consistent with these findings patients receiving MMF had significantly lower FLCκ serum levels compared to patients with CYC induction or controls. Patients receiving MMF to maintain remission had significantly lower FLC serum levels than controls, whereas AZA had no influence on FLC (Tab.1 ). A drastic decrease of FLCκ (p<0.0007), FLCλ (p=0.0017), and PB/PC counts (p<0.0001) was detected in patients who had been on MMF for 16 (10 to 65) weeks. In contrast, no significant change in FLC levels or PB/PC counts was noted 15 (10 to 39) weeks after starting CYC. Inversely, an increase of PB/PC counts was observed 92 (14 to 191) weeks after MMF had been tapered or discontinued (p<0.0001). In the latter patients we also observed rising FLC levels, but this was not significant (FLCκ p=0.0807, FLCλ p=0.0501). Conclusions: Compared to other ID used in patients with SLE, MMF leads to a fast and enduring reduction of PB/PC and FLC. Tapering MMF in clinically quiescent disease is associated with an increase in circulating PB/PC. We currently analyze if increased FLC levels or PB/PC counts predict clinical flares. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2241